Coping with Modi’s India: Nepal’s “pull-distance” Diplomacy (Journal of Interdisciplinary Insights, 2025)
As a small country sandwiched between China and India, Nepal has long been the focus of academic attention regarding its diplomatic thinking and foreign policy. Since the Modi government came to power, the relationship between Nepal and India has witnessed a series of fluctuations, with an overall trajectory characterized by ebbs and flows. India has adopted a more assertive policy towards Nepal, driven by its hegemonic mindset. In contrast, Nepal has pursued a more proactive foreign policy towards India in the context of domestic political stability. This article centers on Nepal’s perspective and employs the concepts of “equidistance diplomacy” and “boomerang effect” to propose an analytical framework of “pull-distance diplomacy” that scrutinizes Nepal’s fundamental logic in implementing its policy toward India across different phases and on various issues. This article argues that Nepal is situated in a “biased distance situation” that tilts towards India in historical and contemporary contexts. However, with the Modi government’s increasingly pronounced hegemonic behavior and the intensifying strategic competition between China and India, Nepal has opted for an active strategy of projecting the boomerang towards China to strengthen its bilateral ties. Nonetheless, the ultimate purpose of this behavior is to signal India and enhance its bargaining power in the negotiation process. Simultaneously, in the process of deploying the boomerang effect, Nepal’s national security and interests have been secured and promoted owing to the strategic pull from India. However, with India resorting to various measures to either lure Nepal closer or exert pressure on it, Nepal may encounter more pressure in the long run.
Keywords: Pull-distance Diplomacy; Nepal-India Interaction; Boomerang Effect